Directions of Deep Brain Stimulation for Epilepsy and Parkinson’s Disease - Wu, Ying-Chang; Liao, Ying-Siou; Yeh, Wen-Hsiu; Liang, Sheng-Fu; Shaw, Fu-Zen (Frontiers in Neuroscience, 2021)
Background: Deep brain stimulation (DBS) is an effective treatment for movement disorders and neurological/psychiatric disorders. DBS has been approved for the control of Parkinson disease (PD) and epilepsy. Objectives: A systematic review and possible future direction of DBS system studies is performed in the open loop and closed-loop configuration on PD and epilepsy. Methods: We searched Google Scholar database for DBS system and development. DBS search results were categorized into clinical device and research system from the open-loop and closed-loop perspectives. Results: We performed literature review for DBS on PD and epilepsy in terms of system development by the open loop and closed-loop configuration. This study described development and trends for DBS in terms of electrode, recording, stimulation, and signal processing. The closed-loop DBS system raised a more attention in recent researches. Conclusion: We overviewed development and progress of DBS. Our results suggest that the closed-loop DBS is important for PD and epilepsy.